Local perception regarding to the environmental assessment and loss of forest resources in the Huasteca region of San Luis Potosi, Mexico - Peralta-Rivero, Carmelo; Galindo-Mendoza, M. Guadalupe; Contreras-Servín, Carlos; Algara-Siller, Marcos; Mas-Caussel, Jean François (Instituto de Ecología, A.C., 2016)
The loss of forest resources in the Mexican Huasteca region is a complex problem, which requires a multidisciplinary approach and a participatory process of local stakeholders in order to detect problems and develop mitigation strategies. The objective of this study is to analyze the local perception of the population regarding the environmental assessment and the loss of forest resources in the Ejido Laguna del Mante and the Tocoy Community of the Huasteca in San Luis Potosi. A methodology for the analysis was developed to evaluate the perception of the local population and semi-structured interviews were applied to stakeholders. Also, a participatory mapping of perception of the past, present and future of the forest resources and other land uses was performed. Finally, in both communities the cover and land uses were classified, and its changes were calculated. The results point out that local population perceives the loss and degradation of their forest resources according to their local knowledge based primarily in the experiences of their productive activities, which is expressed in the interviews and participatory mapping of perception. Both communities suffered considerable deforestation for the period 1973-2014. The methodology based on local perception, supported by participatory mapping and the analysis of land cover and land use change, allowed the understanding of scenarios for the state of forest resources and the productive dynamics developed in the study area. It should serve as a tool for strategies and local policies development towards the conservation and management of the forest covers in the Huasteca.